2018
DOI: 10.1177/1078390317753675
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Physical Activity in an Aquatic Environment During Pregnancy (SWEP Study) and Its Influence in Preventing Postpartum Depression

Abstract: Women who perform moderate physical exercise in an aquatic environment are at lower risk of PPD than sedentary women. Overweight and obesity among sedentary women during pregnancy are closely associated with positive screening for PPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 26 publications
(26 reference statements)
2
47
0
1
Order By: Relevance
“…However, a lower rate of depression was observed among women who were not physically active before the project started and who were included in the intervention group compared to those in the control group. Lower levels of postnatal depression in physically active women in the aquatic environment during pregnancy were also observed in their studies by Aguilar-Cordero et al [50]. The reduction of depression symptoms among women exercising during pregnancy, or pregnancy and puerperium was also noted by Mohammadi et al [49].…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…However, a lower rate of depression was observed among women who were not physically active before the project started and who were included in the intervention group compared to those in the control group. Lower levels of postnatal depression in physically active women in the aquatic environment during pregnancy were also observed in their studies by Aguilar-Cordero et al [50]. The reduction of depression symptoms among women exercising during pregnancy, or pregnancy and puerperium was also noted by Mohammadi et al [49].…”
Section: Discussionsupporting
confidence: 59%
“…Aguilar-Cordero et al [50] examined the influence of physical activity in the aquatic environment on the prevention of postnatal depression. Pregnant women from 20 to 37 weeks participated three times a week in water training according to the SWEP (Study Pregnant Water Exercises) method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found the data regarding association between aquatic exercise and maternal weight control only in four studies selected for this analysis (Aguilar-Cordero et al, 2019;Bacchi, Mottola, Perales, Refoyo, & Barakat, 2018;Backhausen et al, 2014;Vallim et al, 2011). Studies included in this section consistently demonstrated positive impact of involvement in aquatic exercise programs on controlling excessive maternal weight among the samples of pregnant women.…”
Section: Aquatic Exercise Effects On Maternal Weight Controlmentioning
confidence: 94%
“…The following criteria were used for the inclusion of publications in the narrative systematic review: 1) study reported an intervention with at least two points of contact; 2) physical activity was included in the intervention, this included exercise which is a sub-set of PA (e.g., Caspersen et al, 1985;Aguilar-Cordero et al, 2018); 3) studies recruited participants free from chronic health conditions except for obesity; 4) participants were female only or the study presented an analysis segregated by gender; 5) the mean age reported fell within the range of 14 to 25 years; 6) the intervention was UK-based; 7) studies were reported in English language.…”
Section: Inclusion Criteriamentioning
confidence: 99%